2009
DOI: 10.1007/s11926-009-0019-z
|View full text |Cite
|
Sign up to set email alerts
|

A critical reappraisal of allopurinol dosing, safety, and efficacy for hyperuricemia in gout

Abstract: Allopurinol, the first-line drug for serum urate-lowering therapy in gout, is approved by the US Food and Drug Administration for a dose up to 800 mg/d and is available as a low-cost generic drug. However, the vast majority of allopurinol prescriptions are for doses < or = 300 mg/d, which often fails to adequately treat hyperuricemia in gout. This situation has been promoted by longstanding, non-evidence-based guidelines for allopurinol use calibrated to renal function (and oxypurinol levels) and designed, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
91
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 32 publications
1
91
0
1
Order By: Relevance
“…28 However, such doses may not be effective for the treatment of gout. 29 While it is generally recommended that doses be increased from a low dose, 23,24 it has been reported that, in practice, this rarely happens. 27 According to the British Society for Rheumatology, dosing should be based on achieving a target level of serum uric acid of <300µmol/l.…”
Section: Description Of Technology Under Assessmentmentioning
confidence: 99%
“…28 However, such doses may not be effective for the treatment of gout. 29 While it is generally recommended that doses be increased from a low dose, 23,24 it has been reported that, in practice, this rarely happens. 27 According to the British Society for Rheumatology, dosing should be based on achieving a target level of serum uric acid of <300µmol/l.…”
Section: Description Of Technology Under Assessmentmentioning
confidence: 99%
“…79,86 However, allopurinol can also lead to hypersensitivity reactions in children, and should be prescribed with cautious regard for dose. 87 …”
mentioning
confidence: 99%
“…These results support the need of slow titration of the allopurinol dose till the attainment of target levels. A 'dose-escalation' study has shown that a daily dose increment of 300 to 600 mg is associated with serum uric acid levels of <5.5 mg/dL in 78% of patients (68,69). Allopurinol can cause potentially serious adverse reactions such as the hypersensitivity syndrome characterised by cutaneous desquamation, fever, hepatitis, eosinophilia, renail failure and a mortality rate of up to 20% (68,70).…”
Section: Original Articlementioning
confidence: 99%
“…A 'dose-escalation' study has shown that a daily dose increment of 300 to 600 mg is associated with serum uric acid levels of <5.5 mg/dL in 78% of patients (68,69). Allopurinol can cause potentially serious adverse reactions such as the hypersensitivity syndrome characterised by cutaneous desquamation, fever, hepatitis, eosinophilia, renail failure and a mortality rate of up to 20% (68,70). Despite its potential benefit in mild hypersensitivity reactions, desensitisation is not recommended since it is deemed as an obsolete and potentially harmful procedure.…”
Section: Original Articlementioning
confidence: 99%